SURG-12. Endoscopic evaluation of ventricular dissemination in primary central nervous system (CNS) germ cell tumors (GCTs). (3rd June 2022) - Yan, Rachel; Lin, Tong; Carnevale, Joseph; Bhatia, Aashim; Shaw, Dennis; MacDonald, Shannon; Murphy, Erin; Leary, Sarah; Bartels, Ute; Khatua, Soumen; Fouladi, Maryam; Gajjar, Amar; et al.
Abstract: INTRODUCTION: Endoscopic third ventriculostomy and endoscopic tumor biopsy have become integral to the surgical management of children with primary CNS GCTs. Observing ependymal tumor dissemination at the time of endoscopic surgery has been anecdotally reported. The incidence and impact of this finding in CNS GCT has not been reported. METHODS : Baseline neurosurgery data capture forms and operative reports from the Children's Oncology Group (COG) ACNS1123 study were reviewed for ventriculoscopic findings of suspected tumor dissemination. The association between these findings and relapse was determined using Fisher's exact test for each stratum and the Cochran-Mantel-Haenszel test for the entire cohort. Progression-free survival (PFS) was defined as time from enrollment to relapse, progression, death, or last follow-up; and survival probabilities were estimated using the Kaplan-Meier method with log-rank tests for outcome comparisons. RESULTS: 110/244 patients (45.1%) underwent endoscopic neurosurgery. Twelve patients (10.9%) had a documented observation suggestive of metastatic disease within the ventricular compartment. Ten were in the third ventricle and two were in the lateral ventricle. Nine of 12 were nongerminomatous germ cell tumors (NGGCTs) and three were germinoma. Ventriculoscopic findings of metastatic tumor were not significantly associated with relapse in NGGCT (p=0.4091), germinoma (p=0.1832), or overall (p=0.1540); odds ratio 2.57 (95%CI:0.66–10.11). PFS was not influenced in NGGCT (Log-rank test, p=0.1953) but was negatively impacted in germinoma (p=0.0250) when tumor dissemination was found during ventriculoscopy. CONCLUSIONS: Ventriculoscopic observation of tumor dissemination was reported in 10.9% of cases. This may negatively influence outcomes in children with germinoma, though due to the small number of relapses, more data is needed to verify these findings. Ventriculoscopic observation of tumor dissemination may contribute toward more accurate staging and influence future therapy, but a larger sample size is needed. Prospective studies should routinely integrate documentation of endoscopic observation in the study protocol.